Sulfide solid electrolyte powder, solid electrolyte layer, and lithium ion secondary battery

By controlling Al and Zr contents and using high-purity alumina beads, the sulfide solid electrolyte powder maintains particle size and conductivity, addressing contamination issues for improved battery performance.

JP2025008504AActive Publication Date: 2025-01-20AGC INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023110731
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2025-01-20
Estimated Expiration
2043-07-05

AI Technical Summary

Technical Problem

Conventional methods for producing sulfide solid electrolyte powder result in contamination from alumina and zirconia, leading to decreased lithium ion conductivity due to interrupted conduction paths.

Method used

Control the contents of Al and Zr in the sulfide solid electrolyte powder to below 50 ppm each, maintain a particle size D50 of less than 1 μm, and utilize a high-purity alumina bead mill to minimize contamination, ensuring a crystalline phase with an argyrodite or LPS-based crystal structure.

Benefits of technology

Achieves sulfide solid electrolyte powder with enhanced lithium ion conductivity, resulting in improved battery characteristics by maintaining particle size and reducing contamination effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025008504000001_ABST
    Figure 2025008504000001_ABST
Patent Text Reader

Abstract

To provide a sulfide solid electrolyte powder that exhibits excellent lithium-ion conductivity while maintaining its particle size.SOLUTION: The present invention relates to a sulfide solid electrolyte powder in which the content of Al on a mass basis is less than 50 ppm; the content of Zr on a mass basis is less than 50 ppm; and the particle diameter D50 is less than 1 μm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sulfide solid electrolyte powder, a solid electrolyte layer, and a lithium ion secondary battery. [Background technology]

[0002] Lithium ion secondary batteries are widely used in portable electronic devices such as mobile phones and notebook computers. Conventionally, liquid electrolytes have been used in lithium-ion secondary batteries, but all-solid-state lithium-ion batteries (hereinafter also referred to as solid-state batteries), which use solid electrolytes as the electrolyte for lithium-ion secondary batteries, are attracting attention because of the potential for improved safety and high-speed charging and discharging.

[0003] Solid electrolytes are broadly classified into sulfide solid electrolytes and oxide solid electrolytes. Among them, sulfide solid electrolytes exhibit high ionic conductivity because they contain sulfide ions with high polarizability. As a sulfide solid electrolyte, Li 10 GeP 2 S 12 LGPS type crystals such as Li 6 P.S. 5 Argyrodite-type crystals such as Cl, Li 7 P 3 S 11 Crystallized glass such as LPS crystallized glass is known.

[0004] Compared to liquid electrolytes, solid electrolytes have poorer permeability into the positive and negative electrodes. Therefore, in order to improve battery performance, the particle size is reduced or the large coarse particles are eliminated to create a solid electrolyte powder that forms more interfaces with the active material.

[0005] As a technique for reducing the particle size of the solid electrolyte powder, for example, there is a method in which the obtained solid electrolyte or its coarsely pulverized product is pulverized in a wet bead mill using hard beads with a diameter of about 0.1 to 1 mm.

[0006] Examples of types of beads include zirconia beads and alumina beads. However, because zirconia beads have a high specific gravity, they tend to be over-pulverized, which can lead to a decrease in lithium ion conductivity. In contrast, alumina beads have a smaller specific gravity than zirconia beads, and therefore have the advantage that the particle size of the solid electrolyte powder after pulverization is easily maintained. In fact, Patent Document 1 discloses a solid electrolyte obtained by a wet bead mill using alumina beads. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2020 / 105604 Summary of the Invention [Problem to be solved by the invention]

[0008] In response to this, there is a demand for further improvement in lithium ion conductivity for sulfide solid electrolyte powder obtained by pulverizing a sulfide solid electrolyte.

[0009] Therefore, an object of the present invention is to provide a sulfide solid electrolyte powder that exhibits good lithium ion conductivity while maintaining the powder particle size, and a solid electrolyte layer and a lithium ion secondary battery that contain the sulfide solid electrolyte powder. [Means for solving the problem]

[0010] As a result of intensive research, the inventors of the present invention have found that when the sulfide solid electrolyte powder is pulverized using a bead mill to maintain the particle size, the resulting sulfide solid electrolyte powder contains alumina (Al 2 O 3 ) and zirconia (ZrO 2) was found to be present. Further investigation revealed that the above contamination was one of the causes of the decrease in lithium ion conductivity. In other words, the above contamination inhibits the continuity of the sulfide solid electrolyte powder, interrupting the lithium ion conduction path, which is believed to be the cause of the decrease in lithium ion conductivity. In response to this, the inventors have found that the above-mentioned problems can be solved by setting the contents of Al (aluminum) and Zr (zirconium) contained in the sulfide solid electrolyte powder to a certain level or less, and have thus completed the present invention.

[0011] That is, the present invention relates to the following. [1] The content by mass is: Al: Less than 50 ppm, and Zr: Less than 50 ppm The sulfide solid electrolyte powder has a particle size D50 of less than 1 μm. [2] The sulfide solid electrolyte powder according to the above [1], having a BET diameter calculated from a BET specific surface area of ​​0.10 to 0.30 μm. [3] The sulfide solid electrolyte constituting the sulfide solid electrolyte powder has a crystalline phase, The sulfide solid electrolyte powder according to [1] or [2], wherein the crystal phase has an argyrodite-type crystal structure. [4] The sulfide solid electrolyte constituting the sulfide solid electrolyte powder is Li α P.S. β The sulfide solid electrolyte powder according to [1] or [2] above, having a composition represented by (5.5≦α≦5.6, 4.3≦β≦4.4). [5] A solid electrolyte layer comprising the sulfide solid electrolyte powder according to any one of [1] to [4] above. [6] A lithium ion secondary battery comprising the sulfide solid electrolyte powder according to any one of [1] to [4] above. Effect of the Invention

[0012] According to the present invention, a sulfide solid electrolyte powder having excellent lithium ion conductivity while maintaining the powder particle size can be obtained. Therefore, a solid electrolyte layer and a lithium ion secondary battery containing the sulfide solid electrolyte powder can realize excellent battery characteristics due to the excellent lithium ion conductivity. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a flow diagram showing a method for producing a sulfide solid electrolyte powder according to this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be modified as desired without departing from the gist of the present invention. In addition, the symbol "to" indicating a numerical range is used to mean that the numerical values ​​before and after the symbol are included as the lower and upper limits.

[0015] <Sulfide solid electrolyte powder> The sulfide solid electrolyte powder according to the present embodiment satisfies the following contents by mass: Al: less than 50 ppm; Zr: less than 50 ppm. The sulfide solid electrolyte powder also has a particle size D50 of less than 1 μm.

[0016] The particle diameter D50 of the sulfide solid electrolyte powder is less than 1 μm, and is preferably 0.40 μm or more and less than 1 μm. Here, by making the particle diameter D50 less than 1 μm, more interfaces with the active material are formed, improving the battery characteristics. The particle diameter D50 is preferably 0.95 μm or less, more preferably 0.90 μm or less, even more preferably 0.80 μm or less, and particularly preferably 0.70 μm or less. In addition, the lower limit of the particle diameter D50 is not particularly limited, but from the viewpoint of handling, and from the viewpoint of preventing the crystallinity from being easily impaired and realizing good lithium ion conductivity, it is preferably 0.40 μm or more, more preferably 0.45 μm or more, and even more preferably 0.50 μm or more.

[0017] In this specification, the particle size D50 is the volume-based cumulative 50% diameter determined by a laser diffraction particle size distribution measuring device. That is, the particle size distribution is measured by a laser diffraction / scattering method, a cumulative curve is calculated with the total volume of the sulfide solid electrolyte as 100%, and the particle size D50 is the particle size at the point on the cumulative curve where the cumulative volume is 50%. Furthermore, particle size D90 and particle size D10 described later are particle sizes at the points where the cumulative volume is 90% and 10%, respectively, on a cumulative curve obtained by the same measurement as above.

[0018] The particle size D50 of the sulfide solid electrolyte powder is less than 1 μm, which means that the powder can be mass-produced by grinding using a normal bead mill. It is not realistic to obtain a particle size D50 of less than 1 μm by other known grinding means such as mortar grinding, Attritor (registered trademark), disk mill, turbo mill, or vibrating mill.

[0019] In contrast, by using a bead mill using alumina beads or zirconia beads, the particle size D50 can be reduced to less than 1 μm.

[0020] The particle diameter (particle diameter D90) of the sulfide solid electrolyte powder according to this embodiment, which is the point where the cumulative volume is 90% in a volume-based particle size distribution curve, is preferably 0.80 to 3.0 μm, more preferably 0.90 to 2.5 μm, even more preferably 0.90 to 2.0 μm, and particularly preferably 0.90 to 1.8 μm. Here, from the viewpoint of forming more interfaces with the active material and further improving battery characteristics, the particle size D90 is preferably 3.0 μm or less, more preferably 2.5 μm or less, even more preferably 2.0 μm or less, and particularly preferably 1.8 μm or less. In order to prevent the crystallinity of the sulfide solid electrolyte powder from being impaired and to obtain good lithium ion conductivity, the particle size D90 is preferably 0.80 μm or more, and more preferably 0.90 μm or more.

[0021] The particle diameter (particle diameter D10) of the sulfide solid electrolyte powder according to this embodiment, which is the point where the cumulative volume is 10% in the volume-based particle size distribution curve, is preferably 0.10 to 0.80 μm, more preferably 0.15 to 0.70 μm, further preferably 0.20 to 0.65 μm, and particularly preferably 0.25 to 0.60 μm. Here, from the viewpoint of forming more interfaces with the active material and improving battery characteristics, the particle size D10 is preferably 0.80 μm or less, more preferably 0.70 μm or less, even more preferably 0.65 μm or less, and particularly preferably 0.60 μm or less. In order to prevent the crystallinity of the sulfide solid electrolyte powder from being impaired and to obtain good lithium ion conductivity, the particle size D10 is preferably 0.10 μm or more, more preferably 0.15 μm or more, even more preferably 0.20 μm or more, and particularly preferably 0.25 μm or more.

[0022] The BET diameter of the sulfide solid electrolyte powder according to this embodiment calculated from the BET specific surface area is preferably 0.10 to 0.30 μm, more preferably 0.12 to 0.25 μm, and even more preferably 0.13 to 0.23 μm. Here, the BET diameter is preferably 0.10 μm or more, more preferably 0.12 μm or more, and even more preferably 0.13 μm or more, from the viewpoint of preventing the crystallinity of the sulfide solid electrolyte powder from being impaired and obtaining good lithium ion conductivity. From the viewpoint of forming more interfaces with the active material and further improving the battery characteristics, the BET diameter is preferably 0.30 μm or less, more preferably 0.25 μm or less, and even more preferably 0.23 μm or less.

[0023] In this specification, the BET diameter means a particle diameter calculated from a specific surface area measured by the BET method (BET specific surface area) using the following formula. BET diameter (nm) = 6 / [True density (g / cm 3 ) × BET specific surface area (m 2 / g) × 1000 The BET specific surface area is a value determined by a nitrogen adsorption BET multipoint method.

[0024] The BET specific surface area of ​​the sulfide solid electrolyte powder according to this embodiment is 10 to 28 m 2 / g is preferable, and 13 to 26m 2 / g is more preferable, and 13 to 20m 2 / g is more preferred. Here, in order to form more interfaces with the active material and to improve the battery characteristics, the BET specific surface area is set to 10 m 2 / g or more is preferable, and 13m 2 / g or more is more preferable. In addition, in order to prevent the crystallinity of the sulfide solid electrolyte powder from being easily damaged and to obtain good lithium ion conductivity, the BET specific surface area is set to 28 m 2 / g or less is preferable, and 26m 2 / g or less is more preferable, and 20m 2 / g or less is more preferable.

[0025] The particle size D50, BET diameter, and BET specific surface area can be adjusted by appropriately changing the conditions for pulverizing the sulfide solid electrolyte.

[0026] The sulfide solid electrolyte powder according to the present embodiment is an aggregate of sulfide solid electrolyte particles. The sulfide solid electrolyte before pulverization that is the basis of the sulfide solid electrolyte powder according to the present embodiment can be a conventionally known one.

[0027] The sulfide solid electrolyte in this embodiment is specifically Li 7 P 3 S 11 The sulfide solid electrolyte, which has a crystal structure containing Li, P, and S elements and is called the LPS system, Li 10 GeP 2 S 12Examples of the sulfide solid electrolyte include a sulfide solid electrolyte having a crystal structure containing Li, Ge, P, and S elements, which is called LGPS system, such as Li, P, S, and Ha elements, an argyrodite-type crystal structure, a Li-PS-Ha-based sulfide solid electrolyte made of crystallized glass, a sulfide solid electrolyte having a thiolisicone-type crystal structure, and a crystal phase containing an oxide. In addition, the sulfide solid electrolyte may include a crystal phase having the above crystal structure and an amorphous phase. Note that the sulfide solid electrolyte constituting the sulfide solid electrolyte powder according to this embodiment is not limited to the above crystal structure, and some elements may be substituted with other elements.

[0028] Among the above crystal structures, from the viewpoint of lithium ion conductivity and battery characteristics, it is preferable that the sulfide solid electrolyte constituting the sulfide solid electrolyte powder according to the present embodiment has a crystalline phase, and that the crystalline phase has an LPS-based crystal structure or an argyrodite-type crystal structure.

[0029] When the crystal structure of the crystal phase of the sulfide solid electrolyte is an LPS system, the sulfide solid electrolyte is Li α P.S. β It is preferable that the sulfide solid electrolyte powder according to the present embodiment has a composition represented by the formula (5.5≦α≦5.6, 4.3≦β≦4.4). By being a sulfide solid electrolyte powder having an LPS-based crystal structure of the above composition, high lithium ion conductivity can be ensured. Furthermore, the LPS-based crystal structure may contain at least one of Cl and Br elements in addition to Li, P and S elements.

[0030] In the case where the crystal structure of the crystal phase of the sulfide solid electrolyte is an argyrodite type, the argyrodite type crystal structure is a crystal structure having the composition formula Ag 8 GeS 6 This is the crystal structure of a group of compounds derived from minerals represented by the formula:

[0031] When the sulfide solid electrolyte has an argyrodite-type crystal structure, it is more preferable that the Ha element contains at least one element selected from the group consisting of Cl, Br and I, and it is even more preferable that the Ha element contains two or more elements. In the above, it is more preferable that the Ha element contains at least one of Cl and Br, and it is even more preferable that the Ha element contains both Cl and Br.

[0032] The formula for the argyrodite type is Li α’ P.S. β’ Ha γ’ and it is preferable that the element ratios satisfy the relationships of 5≦α'≦7, 4≦β'≦6, and 1.3≦γ'≦2. It is more preferable that the element ratios satisfy the relationships of 5.1<α'<6.3, 4<β'<5.3, and 1.4≦γ'≦1.9, and it is even more preferable that the element ratios satisfy the relationships of 5.2<α'<6.2, 4.1<β'<5.2, and 1.5≦γ'≦1.8. That is, α' is preferably 5 or more, more preferably more than 5.1, and even more preferably more than 5.2, and is preferably 7 or less, more preferably less than 6.3, and even more preferably less than 6.2. β' is preferably 4 or more, more preferably more than 4, and even more preferably more than 4.1, and is preferably 6 or less, more preferably less than 5.3, and even more preferably less than 5.2. γ' is preferably 1.3 or more, more preferably 1.4 or more, and even more preferably 1.5 or more, and is preferably 2 or less, more preferably 1.9 or less, and even more preferably 1.8 or less.

[0033] In the argyrodite-type crystal structure, some of the S element is replaced by Ha and O elements, as well as Se, Te, and BH. 4 , CN, etc. Also, a portion of the P element may be substituted with Si element, Al element, Sn element, In element, Cu element, Sb element, Ge element, etc.

[0034] In this specification, when the sulfide solid electrolyte has an LPS-based crystal structure or an argyrodite-type no crystal structure, it means that the sulfide solid electrolyte has at least these crystal phases.

[0035] The sulfide solid electrolyte according to this embodiment may be a sulfide solid electrolyte including a crystalline phase and an amorphous phase, and the crystallization rate is preferably 80 to 100 mass%, more preferably 85 to 100 mass%, and further preferably 90 to 100 mass%. Here, from the viewpoint of ensuring lithium ion conductivity, the crystallization rate is preferably 80 mass % or more, more preferably 85 mass % or more, and even more preferably 90 mass % or more. From the viewpoint of ensuring lithium ion conductivity, the crystallization rate is preferably high, and may be 100% by mass. In this specification, the crystallinity is the ratio of the crystalline phase to the total ratio of the crystalline phase and the amorphous phase, and can be measured by X-ray diffraction measurement.

[0036] The sulfide solid electrolyte powder according to this embodiment has a mass content of Al: less than 50 ppm and Zr: less than 50 ppm.

[0037] As described above, in order to make the particle size D50 of the sulfide solid electrolyte powder less than 1 μm, fine pulverization using a bead mill is necessary. Here, the vessel of the bead mill is usually made of zirconia-reinforced alumina, with an emphasis on thermal conductivity for cooling. In some cases, it is made of zirconia. Also, the beads (media) of the bead mill are usually made of alumina (Al 2 O 3 ) and zirconia (ZrO 2 ).

[0038] In contrast, when fine pulverization is performed using a bead mill as described above to obtain a sulfide solid electrolyte powder having a particle size D50 of less than 1 μm, Al and Zr derived from the vessel and media are contaminated. Therefore, the content of at least one of Al and Zr in the conventional sulfide solid electrolyte powder is 50 ppm or more by mass. The present inventors have found that the Al and Zr contained as the above-mentioned contaminations are the cause of the decrease in lithium ion conductivity.

[0039] When the sulfide solid electrolyte powder according to the present embodiment contains 50 ppm or more of Al by mass, the ion conduction path is blocked and the lithium ion conductivity is reduced. In contrast, the Al content in the present embodiment is less than 50 ppm by mass, preferably 49 ppm or less, more preferably 20 ppm or less, even more preferably 10 ppm or less, particularly preferably 5 ppm or less, and most preferably 1 ppm or less. The lower limit of the Al content is not particularly limited, but is, for example, 0.01 ppm.

[0040] In addition, when the sulfide solid electrolyte powder according to the present embodiment contains 50 ppm or more of Zr by mass, Zr inhibits the ion conduction path like Al, and reduces the lithium ion conductivity. In contrast, the Zr content in the present embodiment is less than 50 ppm by mass, preferably 49 ppm or less, more preferably 20 ppm or less, even more preferably 10 ppm or less, particularly preferably 5 ppm or less, and most preferably 1 ppm or less. The lower limit of the Zr content is not particularly limited, but is, for example, 0.01 ppm.

[0041] The contents of Al and Zr contained in the sulfide solid electrolyte powder can be measured by ICP (inductively coupled plasma) emission spectrometry, specifically, by the method described in the examples below.

[0042] The above-mentioned Al and Zr contents can be achieved, for example, by subjecting the obtained sulfide solid electrolyte to coarse pulverization, and then further subjecting the coarse pulverized product to fine pulverization using high-purity alumina beads. The high purity is, for example, 99.9% or more.

[0043] The lithium ion conductivity of the sulfide solid electrolyte powder according to this embodiment is preferably 2 mS / cm or more, more preferably 3 mS / cm or more, even more preferably 3.5 mS / cm or more, and particularly preferably 4 mS / cm or more, from the viewpoint of obtaining good battery characteristics when used in a lithium ion secondary battery. The higher the conductivity, the better. The upper limit of the lithium ion conductivity is not particularly limited, but is, for example, 15 mS / cm.

[0044] In this specification, the lithium ion conductivity is a value obtained by measuring a measurement sample obtained by applying a pressure of 380 MPa to the sulfide solid electrolyte powder and compacting it with an AC impedance measuring device. Here, the measurement conditions for the AC impedance measurement are a measurement frequency of 100 Hz to 1 MHz, a measurement voltage of 100 mV, and a measurement temperature of 25°C.

[0045] The sulfide solid electrolyte powder according to the present embodiment is suitably used in an all-solid-state lithium ion secondary battery by treating the sulfide solid electrolyte powder according to the present embodiment by a conventionally known method as desired, and then applying pressure together with a positive electrode active material or a negative electrode active material to form a positive electrode layer or a negative electrode layer, which is an electrode mixture, or by applying pressure together with an additive such as a binder as necessary to form a solid electrolyte layer.

[0046] <Method of manufacturing sulfide solid electrolyte powder> As shown in FIG. 1, the method for producing the sulfide solid electrolyte powder according to this embodiment includes the following steps in order. Step 1: Preparing a sulfide solid electrolyte Step 2: Step S1: Coarsely pulverizing the sulfide solid electrolyte to obtain a coarsely pulverized sulfide solid electrolyte. Step 3: Step S2: finely pulverizing the coarsely pulverized sulfide solid electrolyte to obtain a sulfide solid electrolyte powder.

[0047] Each step will be described below in order.

[0048] ·Process 1 Step 1 is a step of preparing a sulfide solid electrolyte. The sulfide solid electrolyte may be synthesized or may be a commercially available one. When synthesizing the sulfide solid electrolyte, a conventionally known method may be adopted, but a melting method is preferred from the viewpoint of electrolyte homogeneity.

[0049] When synthesizing a sulfide solid electrolyte, it is preferable to include, for example, a step of obtaining a raw material mixture, a step of reacting the raw material mixture, and a step of crystallizing or amorphizing the raw material mixture.

[0050] The reaction in the step of reacting the raw material mixture may be a heating reaction or a mechanochemical reaction. The raw material mixture may be heated to crystallize or amorphize to obtain a sulfide solid electrolyte, in which case a separate crystallization or amorphization step may not be included. In addition to the step of obtaining a crystalline phase or an amorphous phase, the method may include a step of increasing the crystallization rate or a step of rearranging crystals. In the case of the melting method, the raw materials are mixed as necessary, heated to melt, and then cooled to solidify, thereby obtaining a sulfide solid electrolyte.

[0051] The raw materials vary depending on the composition of the desired crystalline phase or amorphous phase, but may include, for example, raw materials containing Li, P, and S. When it is desired to obtain an argyrodite-type crystalline phase containing Ha or an LPSHa-type crystallized glass containing Ha, a raw material containing Ha in addition to Li, P, and S may be used.

[0052] Specifically, for example, when obtaining argyrodite-type crystals or Li-PS-Ha-based crystallized glass, raw materials containing Li, P, S, and Ha are used. 7 P 3 S 11 When obtaining LPS crystals or LPS glass-ceramics such as those described above, raw materials containing Li, P, and S are used. 10 GeP 2 S 12 When obtaining LGPS-based crystals such as those described above, raw materials containing Li, Ge, and S are used. When obtaining thiolisicone-type crystals, raw materials containing Li, S, Ge, and P are used. The above raw materials may each be any of those known in the art. The conditions for mixing and reacting the raw materials may be those known in the art. For example, in the case of a melting method, the heating temperature during heating and melting, the time during heating and melting or cooling and solidifying, the atmosphere, pressure, dew point, and the like may be those known in the art. Alternatively, an intermediate may be used in which the raw materials are reacted before being melted, and melt synthesis may be carried out from the intermediate.

[0053] ·Process 2 Step 2 is a step of roughly pulverizing the sulfide solid electrolyte obtained in step 1 to obtain a roughly pulverized sulfide solid electrolyte (step S1). In order to obtain a sulfide solid electrolyte powder having a particle size D50 of less than 1 μm by fine pulverization in step 3 described below, the material is coarsely pulverized in step 2 to approximately one-tenth the diameter of the beads, which are the media used in the bead mill in step 3.

[0054] As a method for coarse pulverization, a method other than wet pulverization is preferable, for example, a cutter mill (cut mill) is preferable. A cutter mill is a method of pulverizing raw materials by rotating a rotor equipped with cutters at high speed and using shearing or cutting forces.

[0055] In the cutter mill, for example, by using stainless steel crushing blades coated with a low-wear coating material, contamination of stainless steel components can be suppressed. In addition, unlike coarse grinding using a planetary ball mill, coarse grinding using a cutter mill does not require the use of alumina or zirconia balls, so the Al and Zr contents in the finally obtained sulfide solid electrolyte powder can be suitably reduced.

[0056] Moreover, other than the coarse pulverization using a cutter mill, for example, a method of obtaining a coarse powder directly from a melt may be used to obtain something equivalent to a coarsely pulverized material.

[0057] In addition, coarse pulverization using a bead mill using easily worn alumina beads (for example, alumina beads with a purity of 99.5% or less and a Vickers hardness HV10 of 1,300 or less) or zirconia beads results in high Al and Zr contents in the coarsely pulverized sulfide solid electrolyte. As a result, it is difficult to make the Al content and Zr content of the resulting sulfide solid electrolyte powder both less than 50 ppm by mass.

[0058] The coarse pulverization is preferably carried out so that the particle size D95 of the coarsely pulverized sulfide solid electrolyte is less than 100 μm. This is because it is suitable for the bead mill pulverization in step 3. Specifically, depending on the model, bead mills are equipped with a filter called a screen at the exit of the grinding chamber to pass only the slurry and separate it from the beads. It is preferable to use a filter with a gap of about 100 μm or less.

[0059] The size of the gaps in the filter can be selected, but when it is desired to obtain particularly fine powder as in the present embodiment, it is preferable to use small beads, such as beads with a diameter of 0.3 mm, rather than beads with a diameter of 0.5 mm. In that case, taking into consideration the dimensional error of the beads, the size of the gaps in the filter needs to be 100 μm, rather than 200 μm.

[0060] Therefore, the particle size D95 of the coarsely ground product obtained in step 2 is preferably at least less than 100 μm to prevent clogging of the filter. The coarse pulverization is preferably carried out so that the particle size D95 of the coarsely pulverized product is 10 to 99 μm, more preferably 10 to 70 μm, and even more preferably 10 to 50 μm. From the viewpoint of preventing clogging of the filter (screen) at the outlet of the pulverization chamber, the particle size D95 of the coarsely pulverized product is preferably less than 100 μm, more preferably 99 μm or less, even more preferably 70 μm or less, and even more preferably 50 μm or less. From the viewpoint of preventing an increase in viscosity of the slurry containing the coarsely pulverized product and a solvent to be subjected to step 3 and preventing aggregation of the coarsely pulverized product, the particle size D95 is preferably 10 μm or more.

[0061] From the viewpoint of preventing filter clogging, the particle size D50 of the coarsely pulverized product obtained in step 2 is preferably 5 to 30 μm, more preferably 8 to 20 μm. Here, the particle size D50 is preferably 30 μm or less, more preferably 20 μm or less, and is preferably 5 μm or more, more preferably 8 μm or more.

[0062] After the sulfide solid electrolyte is coarsely pulverized, classification (sieving, etc.) may be performed as necessary to obtain a coarsely pulverized sulfide solid electrolyte.

[0063] ·Process 3 Step 3 is a step of finely pulverizing the coarsely pulverized sulfide solid electrolyte obtained in step 2 to obtain a sulfide solid electrolyte powder (step S2).

[0064] The fine pulverization is preferably performed using a bead mill. Depending on the type, a bead mill is a method of producing fine powder by so-called collision pulverization, in which hard beads are rotated in a cylindrical container and the beads collide with the material to crush it, thereby producing fine powder. By selecting an appropriate bead size using this method and performing fine pulverization, a fine sulfide solid electrolyte powder with a particle size D50 of less than 1 μm can be obtained.

[0065] The type of beads for fine grinding is preferably high-purity alumina beads, from the viewpoint of obtaining fine sulfide solid electrolyte powder having good lithium ion conductivity, and from the viewpoint of suppressing contamination with aluminum or zirconium and improving lithium ion conductivity.

[0066] In addition, from the viewpoint of reducing wear of the aluminum beads and suppressing aluminum contamination, the high purity alumina beads preferably satisfy at least one of a purity of 99.9% or more and a Vickers hardness of 1800HV10 or more, and more preferably satisfy both. By using such high purity alumina beads, wear of the vessel due to the beads can be further suppressed, and therefore contamination of the zirconium sulfide solid electrolyte powder contained in the vessel can also be suppressed.

[0067] The purity of the alumina beads is preferably 99.9% or more, more preferably 99.93% or more, further preferably 99.95% or more, and particularly preferably 99.99% or more, and the higher the purity the more preferable.

[0068] The Vickers hardness of the alumina beads is preferably 1800HV10 to 2300HV10. From the viewpoint of wear resistance, the Vickers hardness is preferably 1800HV10 or more, more preferably 1900HV10 or more, even more preferably 2000HV10 or more, and particularly preferably 2100HV10 or more. From the viewpoint of suppressing wear of the grinding chamber (vessel) and rotor, the Vickers hardness is preferably 2300HV10 or less.

[0069] The purity of alumina beads can be measured by measuring the amount of impurities using ICP emission spectroscopy and subtracting the total amount of impurities from 100%. Vickers hardness can be measured by pressing a pyramidal diamond indenter against a test piece, observing the indentation under a microscope, and measuring the length of the diagonal line.

[0070] In addition, the fine pulverization may be either dry pulverization or wet pulverization using a dispersion medium, but wet pulverization is preferred from the viewpoint of obtaining a finer sulfide solid electrolyte powder with a particle size D50 of less than 1 μm. Dry pulverization is suitable for obtaining a powder with a particle size D50 of 1 to 3 μm, while wet pulverization is suitable for obtaining a fine powder with a particle size D50 of less than 1 μm.

[0071] In the wet grinding method, the coarsely ground sulfide solid electrolyte may be dispersed or dissolved in a dispersion medium to form a slurry, and then ground. In addition to the sulfide solid electrolyte solvent, additives such as a dispersant may be further added to the slurry.

[0072] The dispersion medium is not particularly limited, but since the sulfide solid electrolyte has a tendency to react with moisture and deteriorate, a non-aqueous solvent is preferred.

[0073] The type of non-aqueous organic solvent is not particularly limited, and examples thereof include hydrocarbon solvents, organic solvents containing a hydroxy group, organic solvents containing an ether group, organic solvents containing a carbonyl group, organic solvents containing an ester group, organic solvents containing an amino group, organic solvents containing a formyl group, organic solvents containing a carboxy group, organic solvents containing an amide group, organic solvents containing a benzene ring, organic solvents containing a mercapto group, organic solvents containing a thioether group, organic solvents containing a thioester group, organic solvents containing a disulfide group, and alkyl halides.

[0074] Examples of the hydrocarbon solvent include cyclohexane, heptane, octane, and toluene, and from the viewpoint of low saturated water concentration, cyclohexane, heptane, and octane are preferred. From the viewpoint of adjusting the water concentration, it is also preferred to mix these hydrocarbon solvents with toluene, dibutyl ether, or the like to form a mixed solvent.

[0075] In order to prevent a decrease in lithium ion conductivity due to a reaction between the sulfide solid electrolyte and water during fine pulverization of the coarsely pulverized sulfide solid electrolyte, the water concentration in the dispersion medium is preferably low. The water concentration of the dispersion medium may be, for example, 170 ppm by mass or less, 150 ppm by mass or less, 120 ppm by mass or less, or 100 ppm by mass or less.

[0076] When a dispersant is used as the additive, examples of the dispersant include an ether compound, an ester compound, and a nitrile compound.

[0077] The content of the coarsely pulverized sulfide solid electrolyte in the slurry is preferably 5 to 35 mass%, more preferably 10 to 33 mass%, and even more preferably 20 to 30 mass%. From the viewpoint of pulverization efficiency and ease of handling of the slurry, the content is preferably 5 mass% or more, more preferably 10 mass% or more, and even more preferably 20 mass% or more, and is preferably 35 mass% or less, more preferably 33 mass% or less, and even more preferably 30 mass% or less.

[0078] The solid content in the slurry is preferably 5 to 35% by mass, more preferably 10 to 33% by mass, and even more preferably 20 to 30% by mass. From the viewpoint of grinding efficiency and ease of handling of the slurry, the solid content is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 20% by mass or more, and is preferably 35% by mass or less, more preferably 33% by mass or less, and even more preferably 30% by mass or less.

[0079] When the fine pulverization is performed by a wet bead mill, the diameter of the beads for fine pulverization is preferably 0.1 to 1 mm, more preferably 0.2 to 0.8 mm, and even more preferably 0.3 to 0.5 mm. From the viewpoint of obtaining a sulfide solid electrolyte powder having good lithium ion conductivity, the diameter is preferably 0.1 mm or more, more preferably 0.2 mm or more, and even more preferably 0.3 mm or more. From the viewpoint of obtaining a finely pulverized product having a desired small particle size, the diameter is preferably 1 mm or less, more preferably 0.8 mm or less, and even more preferably 0.5 mm or less.

[0080] When the fine pulverization is performed using a wet bead mill, the rotational speed of the mill is preferably 6 to 12 m / sec, more preferably 8 to 10 m / sec. By setting the rotational speed of the mill within the above range, excessive pulverization of the sulfide solid electrolyte can be prevented, and aggregation of particles in the sulfide solid electrolyte powder can be suppressed.

[0081] The grinding time by the wet bead mill depends on the amount of the coarsely ground material to be ground, but for example, when the amount of the coarsely ground material is about 150 to 165 g, it is preferably 30 to 480 minutes, more preferably 60 to 240 minutes. From the viewpoint of reducing the particle size of the sulfide solid electrolyte powder, the grinding time is preferably 30 minutes or more, more preferably 60 minutes or more. From the viewpoint of suppressing over-grinding and ensuring good lithium ion conductivity, the grinding time is preferably 480 minutes or less, more preferably 240 minutes or less.

[0082] A drying step may be further carried out on the sulfide solid electrolyte powder obtained in step 3. By drying, even if the dispersion medium or additives remain in the sulfide solid electrolyte powder, they can be removed. The drying method can be a conventionally known method, for example, a hot plate, a drying oven, an electric oven, or the like.

[0083] The temperature in the drying step is not particularly limited, and may be, for example, 50 to 300° C. When fine pulverization is performed using a dispersion medium, drying may be performed by heating at a temperature equal to or higher than the boiling point of the dispersion medium. The time for the drying step is not particularly limited, but may be, for example, 10 minutes to 24 hours. The drying step may be carried out under reduced pressure, for example, at an absolute pressure of 50 kPa or less.

[0084] Furthermore, a heat treatment (annealing treatment) may be performed on the sulfide solid electrolyte powder obtained in step 3. By performing the annealing treatment, the lithium ion conductivity can be improved. The temperature and time of the annealing treatment can be appropriately adjusted, but may be, for example, performed at 200 to 600° C. for 10 to 600 minutes. The heat treatment may be performed between step 2 and step 3.

[0085] <Solid electrolyte layer> The sulfide solid electrolyte powder according to the present embodiment may be used in a solid electrolyte layer. That is, the solid electrolyte layer according to the present embodiment includes the sulfide solid electrolyte powder described in the above <Sulfide solid electrolyte powder>, and preferred aspects are also the same.

[0086] The solid electrolyte layer according to this embodiment is preferably used in a lithium ion secondary battery. Furthermore, the solid electrolyte layer according to this embodiment may contain a binder, if necessary.

[0087] The content of the sulfide solid electrolyte powder in the solid electrolyte layer according to the present embodiment is not particularly limited and may be appropriately determined depending on the performance of the target battery. For example, the content of the sulfide solid electrolyte powder is preferably 80 mass% or more, more preferably 90 mass% or more, relative to the entire solid electrolyte layer.

[0088] Examples of binders that can be contained in the solid electrolyte layer include butadiene rubber (BR), acrylate butadiene rubber (ABR), styrene butadiene rubber (SBR), polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), etc. The content of the binder in the solid electrolyte layer may be the same as that of a conventional binder.

[0089] The thickness of the solid electrolyte layer is not particularly limited and may be appropriately determined depending on the performance of the intended battery. For example, the thickness is preferably 10 to 50 μm, more preferably 15 to 20 μm. Here, from the viewpoint of obtaining a solid electrolyte layer having increased mechanical strength, resistance to stress such as vibration and bending, and high reliability, the thickness is preferably 10 μm or more, more preferably 15 μm or more. Moreover, from the viewpoint of increasing the ion conductivity between the positive and negative electrodes and increasing the energy density of the battery, the thickness is preferably 50 μm or less, more preferably 20 μm or less.

[0090] The method for forming the solid electrolyte layer is not particularly limited. For example, the components constituting the solid electrolyte layer described above are dispersed or dissolved in a liquid medium to form a slurry, which is then coated in a layer (sheet), dried, and optionally pressed to form the solid electrolyte layer. If necessary, a binder removal treatment may be performed by applying heat. The thickness of the solid electrolyte layer can be easily adjusted by adjusting the coating amount of the slurry, etc.

[0091] Instead of the wet molding as described above, the solid electrolyte layer may be formed by dry press molding of a solid electrolyte powder or the like on the surface of the object (positive electrode, negative electrode, etc.) on which the solid electrolyte layer is to be formed. Alternatively, the solid electrolyte layer may be formed on another substrate, which is then transferred to the surface of the object on which the solid electrolyte layer is to be formed. From the viewpoint of being able to industrially and stably form a strong solid electrolyte layer on the surface of the object on which the solid electrolyte layer is to be formed, it is preferable to form the solid electrolyte layer on the surface of the object by wet molding using a liquid medium.

[0092] <Lithium-ion secondary battery> The sulfide solid electrolyte powder according to the present embodiment may be used in a lithium ion secondary battery. That is, the lithium ion secondary battery according to the present embodiment includes the sulfide solid electrolyte described in the above <Sulfide solid electrolyte powder>, and preferred aspects are also the same.

[0093] The lithium ion secondary battery according to the present embodiment includes a solid electrolyte layer, a positive electrode layer, and a negative electrode layer. The sulfide solid electrolyte powder may be contained in at least one of the solid electrolyte layer, the positive electrode layer, and the negative electrode layer, or may be contained in at least two of the solid electrolyte layer, the positive electrode layer, and the negative electrode layer, or may be contained in all of the solid electrolyte layer, the positive electrode layer, and the negative electrode layer. Other than the sulfide solid electrolyte powder, the solid electrolyte layer, the positive electrode layer, and the negative electrode layer may be made of any of the conventionally known materials. Specific examples are shown below, but the present invention is not limited to these.

[0094] (Positive electrode layer) The positive electrode layer contains at least a positive electrode current collector and a positive electrode active material. The positive electrode layer may further contain the sulfide solid electrolyte powder according to the present embodiment.

[0095] The positive electrode current collector may be any conductive plate material, for example, a thin metal plate (metal foil) of aluminum or an alloy thereof, stainless steel, etc. These are preferred because they have excellent electrolyte resistance and oxidation resistance.

[0096] The positive electrode active material is a material that absorbs and releases lithium ions, removes and inserts lithium ions (intercalates), or has a counter anion (e.g., PF 6 - As long as the doping and dedoping of lithium cobalt oxide (LiCoO) can be performed reversibly, the positive electrode active material is not particularly limited, and a known positive electrode active material can be used. 2 ), lithium nickel oxide (LiNiO 2 ), lithium manganese oxide (LiMnO 2 ), lithium nickel manganese oxide, Li(Ni x Co y Mn z M a )O 2(x+y+z+a=1, 0≦x≦1, 0≦y≦1, 0≦z≦1, 0≦a≦1, and M is at least one selected from Al, Mg, Nb, Ti, Cu, Zn, and Cr), Li a M b (PO 4 ) c (1≦a≦4, 1≦b≦2, 1≦c≦3, and M is at least one selected from Fe, V, Co, Mn, Ni, and VO).

[0097] The positive electrode layer may contain a binder that binds the positive electrode active materials together and also binds the positive electrode active material to the positive electrode current collector. Conventionally known binders can be used as the binder. The positive electrode layer may also contain a known conductive assistant for positive electrodes, examples of which include carbon-based materials such as graphite and carbon black, metals such as copper, nickel, stainless steel, and iron, and conductive oxides such as indium tin oxide (ITO).

[0098] (Negative electrode layer) The negative electrode layer contains at least a negative electrode current collector and a negative electrode active material. The negative electrode layer may further contain the sulfide solid electrolyte powder according to the present embodiment.

[0099] The negative electrode current collector may be any conductive plate material, for example, a thin metal plate (metal foil) of copper, aluminum, etc. These are preferred because they have excellent electrolyte resistance and oxidation resistance.

[0100] The negative electrode active material is not particularly limited, and may be any material capable of inserting and extracting lithium ions, such as lithium metal, carbon-based materials, silicon, silicon alloys, and tin. The negative electrode active material is a material that absorbs and releases lithium ions, removes and inserts lithium ions (intercalates), or has a counter anion of the lithium ion (e.g., PF 6 -As long as the doping and dedoping of lithium can be carried out reversibly, the negative electrode active material is not particularly limited, and a known negative electrode active material can be used. Examples of the negative electrode active material include carbon-based materials such as graphite, hard carbon, and soft carbon; metals that can form alloys with lithium, such as aluminum, silicon, and tin; amorphous oxides, such as silicon oxide and tin oxide; and lithium titanate (Li 4 Ti 5 O 12 ) etc.

[0101] In addition, the negative electrode layer may contain a binder that binds the negative electrode active materials together and also binds the negative electrode active material to the negative electrode current collector. Conventionally known binders can be used as the binder. The negative electrode layer may contain a known conductive assistant for negative electrodes, and the same conductive assistant for positive electrodes as above can be used.

[0102] The components constituting the lithium ion secondary battery, such as the solid electrolyte layer, the positive electrode layer, and the negative electrode layer, are housed in a battery exterior body. The material of the battery exterior body may be a conventionally known material, and specific examples thereof include nickel-plated iron, stainless steel, aluminum or alloys thereof, nickel, titanium, resin materials, and film materials.

[0103] The shape of the lithium ion all-solid-state battery may be a coin type, a sheet type (film type), a folded type, a wound type with a bottom, a cylindrical type, a button type, etc., and can be appropriately selected depending on the application.

[0104] The lithium ion secondary battery according to this embodiment can achieve good lithium ion conductivity. EXAMPLES

[0105] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. Example 1 is an example, and Example 2 is a comparative example.

[0106] <Test Example> (Example 1) Under a dry nitrogen atmosphere, Li 5.4 P.S. 4.4Cl 0.8 Br 0.8 Lithium sulfide powder (Sigma, purity 99.98%), diphosphorus pentasulfide powder (Sigma, purity 99%), lithium chloride powder (Sigma, purity 99.99%), and lithium bromide powder (Sigma, purity 99.995%) were weighed out to obtain the composition, placed in a quartz test tube, and vacuum sealed. After dissolving at 750°C for 1 hour, the mixture was cooled to obtain a sulfide solid electrolyte. The obtained sulfide solid electrolyte was coarsely pulverized with a cutter mill to obtain a coarsely pulverized sulfide solid electrolyte. Next, 165 g of the crudely ground sulfide solid electrolyte obtained above was added to 385 g of dehydrated dibutyl ether to obtain a slurry (slurry solid content concentration: 30 mass%). 550 g of the slurry and 288 g of high-purity alumina beads with a diameter of 0.3 mm (Taimei Chemical, TB-03, purity 99.99 mass% or more) were placed in a zirconia-reinforced alumina sample container (vessel), which was then set in a Labostar Mini LMZ015 manufactured by Ashizawa Finetech Co., Ltd., and wet-pulverized under the following conditions. (conditions) Bead filling rate in sample container: 70.2% by volume ·Peripheral speed: 8m / sec Grinding time: 240 minutes Slurry flow rate: approx. 1L / min Thereafter, the mixture was heated at a temperature equal to or higher than the boiling point of the solvent in a nitrogen atmosphere and dried to obtain a sulfide solid electrolyte powder.

[0107] (Example 2) A sulfide solid electrolyte powder of Example 2 was obtained in the same manner as in Example 1, except that alumina beads having a diameter of 0.3 mm and a purity of 99.5 mass% (AL9-0.3 manufactured by Hira Ceramics Co., Ltd.) were used instead of the high-purity alumina beads having a diameter of 0.3 mm.

[0108] <Evaluation> [Particle size distribution: particle size D50, particle size D90] The particle sizes D10, D50, and D90 in the volume-based cumulative particle size distribution were measured using a laser diffraction particle size distribution measuring device, Microtrac MT3300EX II manufactured by Microtrac Bell, and a very small volume circulator, Microtrac USVR.

[0109] [BET diameter] The BET specific surface area was measured by the nitrogen adsorption BET multipoint method, and the value calculated by the following formula was taken as the BET diameter. BET diameter (nm) = 6 / [True density (g / cm 3 ) × BET value (m 2 / g) × 1000

[0110] [Lithium ion conductivity] The sulfide solid electrolyte powder was pressed under a pressure of 380 MPa and used as a measurement sample. Measurements were carried out under the following conditions using an AC impedance measuring device (potentiostat / galvanostat VSP, manufactured by Bio-Logic Sciences Instruments). Measurement frequency: 100Hz~1MHz Measurement voltage: 100mV Measurement temperature: 25℃ The lithium ion conductivity at 25° C. was determined from the obtained Nyquist plot.

[0111] [Al content and Zr content] The sulfide solid electrolyte powder was dissolved in an alkali and turned into a solution. The residue generated during the dissolution process was collected and dissolved in acid to turn it into a solution. The Al and Zr in each solution were quantified by ICP (inductively coupled plasma) emission spectrometry to obtain the Al content and Zr content in the powder.

[0112] [Crystallinity] The sulfide solid electrolyte powder was measured by X-ray diffraction (XRD), and the ratio of the crystalline phase to the total of the crystalline phase and the amorphous phase was taken as the crystallization ratio.

[0113] [Table 1]

[0114] As shown in Table 1, the sulfide solid electrolyte powder of Example 1, in which high-purity alumina beads were used during fine pulverization, had significantly reduced Al and Zr contents compared to the sulfide solid electrolyte of Example 2, which is a comparative example, and also achieved high lithium ion conductivity.

Claims

1. The content by mass is: Al: less than 50 ppm, and Zr: less than 50 ppm; A sulfide solid electrolyte powder having a particle size D50 of less than 1 μm.

2. The sulfide solid electrolyte powder according to claim 1, wherein the BET diameter calculated from the BET specific surface area is 0.10 to 0.30 μm.

3. The sulfide solid electrolyte constituting the sulfide solid electrolyte powder has a crystalline phase, The sulfide solid electrolyte powder according to claim 1 , wherein the crystal phase has an argyrodite-type crystal structure.

4. The sulfide solid electrolyte constituting the sulfide solid electrolyte powder is Li α P.S. β The sulfide solid electrolyte powder according to claim 1, having a composition represented by (5.5≦α≦5.6, 4.3≦β≦4.4).

5. A solid electrolyte layer comprising the sulfide solid electrolyte powder according to any one of claims 1 to 4.

6. A lithium ion secondary battery comprising the sulfide solid electrolyte powder according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Manufacturing method of sulfide solid electrolyte particle

    JP2019186129A

  • Sulfide solid electrolyte and production method thereof

    WO2021132537A1

  • Solid electrolyte, electrode mix, solid electrolyte layer, and all-solid-state battery

    WO2020105604A1